Regulatory Frameworks for Cross-Border Telemedicine Services: Navigating the Global Digital Health Landscape - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The capability of cross-border telemedicine, driven by advancements in Artificial Intelligence AI and remote monitoring, promises to democratize access to sp...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics